THE ROLE OF INVESTMENT OPPORTUNITIES, MANAGERIAL OWNERSHIP, CAPITAL STRUCTURE ON CORPORATE VALUE - Septiana, Darlene Dacia; Riswandari, Ernie (Universitas Pamulang, 2020)
There are still companies that pay less attention and maintain value of ownership even though this is a concern in making investment decisions. In this study will examine investment opportunities, capital structure, and managerial ownership of firm value. The sample used is the financial statements of 27 companies manufacturing consumer goods sub sector in 2015-2017. This research is an associative research using secondary data which is quantitative data. Data is processed using Stata 12 by using multiple linear regression tests. The results showed that investment opportunities, capital structure, and managerial ownership had a significant effect on the firm's value partially on companies manufacturing the consumer goods sub sector.